1993
DOI: 10.1128/jvi.67.7.3923-3930.1993
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response to hypervariable region 1 of the putative envelope glycoprotein (gp70) of hepatitis C virus

Abstract: We recently found that alterations of amino acids in hypervariable region 1 (HVR1) of the putative envelope glycoprotein (gp70) of hepatitis C virus (HCV) occurred sequentially in the chronic phase of hepatitis at intervals of several months. This finding suggests that mutations in HVR1 are involved in the mechanism of persistent chronic HCV infection involving escape from the immunosurveillance system. To explore this possibility, we examined the humoral immune response to HVR1 with our assay system, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0
2

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(143 citation statements)
references
References 47 publications
7
134
0
2
Order By: Relevance
“…Thus, the more rapid evolution of HVR1 in the acute hepatitis period could reflect the presence of neutralizing antibodies directed at the viral envelope. Indeed, epitopes are present in some HVR1 sequences that induce the formation of humoral antibodies, 26,[28][29][30][31] and neutralizing activity has been shown with antibodies directed against particular HVR1 sequences. 7,27,32,33 The observed evolution of HVR1 also could be caused by the activity of HCV-specific CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the more rapid evolution of HVR1 in the acute hepatitis period could reflect the presence of neutralizing antibodies directed at the viral envelope. Indeed, epitopes are present in some HVR1 sequences that induce the formation of humoral antibodies, 26,[28][29][30][31] and neutralizing activity has been shown with antibodies directed against particular HVR1 sequences. 7,27,32,33 The observed evolution of HVR1 also could be caused by the activity of HCV-specific CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…HVR1 contains one of the principal HCV-neutralizing epitopes and also appears to be a target for cytotoxic responses. [110][111][112][113] We showed that IFN-␣ administration and subsequent withdrawal result in shifts of HVR1 nucleotide sequences in more than 70% of patients infected with the most frequent HCV genotypes (i.e., 1a, 1b, 2a, 2c, 3a, and 4a) receiving IFN-␣ in monotherapy. 79 Similar changes are observed in patients receiving the combination of IFN-␣ and ribavirin.…”
Section: Consequences Of Hcv Resistance To Ifnmentioning
confidence: 99%
“…However, antibodies against a single E2 HVR1 are isolate-specific, 24 and lead to the emergence of escape mutants during chronic infection. [16][17][18][19][20][21] Because of the large inter-and intra-individual heterogeneity of this viral region, a major task in developing an HCV vaccine would be to generate an immunogen that induces highly cross-reactive anti-HVR1 response to prevent outgrowth of escape mutants, rather than require the immune system to deal with them after they arise. In this work, we have tested several plasmids encoding HCV E2 to evaluate their potential of inducing a cross-reacting anti-HVR1 response.…”
Section: Discussionmentioning
confidence: 99%
“…10 In fact, HCV displays a high rate of mutation during replication and exists in the bloodstream of infected patients as a quasispecies, [11][12][13][14][15] which fluctuates during the course of the disease mainly as a result of immune pressure. [15][16][17][18][19][20][21][22][23] The major target of this immune response is the 27 amino acid-long N-terminal segment of the E2 glycoprotein. This protein fragment is the most variable region of the whole HCV polyprotein 11 and contains a principal neutralization determinant, 24 but anti-hypervariable region 1 (HVR1) antibodies specific for one variant display only a limited ability to block different viral variants.…”
mentioning
confidence: 99%